(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2019)
Strengthening critical thinking in students in the Early Childhood Education program at the University of Pamplona focuses on identifying teachers’ needs in pedagogical processes in order to stimulate critical thinking in students. The research was framed within qualitative research, using the Action_Pedagogical research method, under the postulates of Gómez (2009), Paul & Elder (2003), Facione (2007), Porlán (1997), Moreno and Azcarate (2003), among others. Two instruments were used as techniques: the semi-structured interview and the field diary, which records observations related to teaching work during academic sessions, in order to understand their needs on the subject. This allows us to offer an academic proposal with guidelines to the institution to strengthen this skill in students.